Demographic factors of corporate E-learning among E-learners in an oil and gas company - Balakrishnan, Sharmini Marilyn; Mohd Puad, Mohd Hazwan; Ab Jalil, Habibah (TURKBILMAT Education Services, 2021)
rganizations that use e-learning as a tool to educate their employees have either reaped the benefits or struggled with its implementation. The dominant reason for this is corporate e-learning overlaps the organizational, human, and technological aspects of learning. Previous research has compartmentalized the research by studying these three aspects separately, so there is little insight on how these variables affect corporate e-learning. Therefore, this study aimed to assess the levels and differences of organizational learning, e-learning quality, and e-learning use according to the demographic groups of corporate e-learners in a Malaysian oil and gas company. A quantitative survey method was applied to collect data from 261 participants using a 5-point Likert Scale questionnaire. The results revealed the level of overall organizational learning, e-learning quality, and e-learning use was moderate. Furthermore, organizational learning, e-learning quality, and e-learning use were significantly different for gender, department, and job position demographic groups. However, age and working experience did not show a significant difference for these variables. The findings from this study provide a bottom-up insight to stakeholders and managers when investing in and implementing e-learning at the organization.